2010
DOI: 10.1371/journal.pone.0012444
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Whaling on the Ocean Carbon Cycle: Why Bigger Was Better

Abstract: BackgroundHumans have reduced the abundance of many large marine vertebrates, including whales, large fish, and sharks, to only a small percentage of their pre-exploitation levels. Industrial fishing and whaling also tended to preferentially harvest the largest species and largest individuals within a population. We consider the consequences of removing these animals on the ocean's ability to store carbon.Methodology/Principal FindingsBecause body size is critical to our arguments, our analysis focuses on popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
135
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(138 citation statements)
references
References 49 publications
(62 reference statements)
0
135
1
2
Order By: Relevance
“…Emerging evidence suggests that mobile marine species can transform the environment as they move through it, transferring nutrients within the water column (deep to shallow and vice versa) and across oceans (Wilson et al, 2009;Pershing et al, 2010;Roman and McCarthy, 2010;Roman et al, 2014;St John et al, 2016). For example, depletion of whales due to commercial whaling resulted in substantial deep-sea habitat loss through a reduction in dead whale "falls" (Smith, 2007), declines in primary productivity due to reduced nutrient shuttling Roman and McCarthy, 2010), changes in food-web structure and biogeochemical cycles (Lavery et al, 2010;Roman and McCarthy, 2010), and reduced potential for organic carbon sequestration (Lavery et al, 2010;Pershing et al, 2010).…”
Section: Habitats As a Function Of Their Inhabitantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence suggests that mobile marine species can transform the environment as they move through it, transferring nutrients within the water column (deep to shallow and vice versa) and across oceans (Wilson et al, 2009;Pershing et al, 2010;Roman and McCarthy, 2010;Roman et al, 2014;St John et al, 2016). For example, depletion of whales due to commercial whaling resulted in substantial deep-sea habitat loss through a reduction in dead whale "falls" (Smith, 2007), declines in primary productivity due to reduced nutrient shuttling Roman and McCarthy, 2010), changes in food-web structure and biogeochemical cycles (Lavery et al, 2010;Roman and McCarthy, 2010), and reduced potential for organic carbon sequestration (Lavery et al, 2010;Pershing et al, 2010).…”
Section: Habitats As a Function Of Their Inhabitantsmentioning
confidence: 99%
“…For example, depletion of whales due to commercial whaling resulted in substantial deep-sea habitat loss through a reduction in dead whale "falls" (Smith, 2007), declines in primary productivity due to reduced nutrient shuttling Roman and McCarthy, 2010), changes in food-web structure and biogeochemical cycles (Lavery et al, 2010;Roman and McCarthy, 2010), and reduced potential for organic carbon sequestration (Lavery et al, 2010;Pershing et al, 2010). The consequences of extraction therefore extended far beyond the decline of individual whale species.…”
Section: Habitats As a Function Of Their Inhabitantsmentioning
confidence: 99%
“…Of course, this idea assumes that: (i) a reduction of fishing effort would increase those ES, and (ii) the corresponding increases in value would exceed the value lost by commercial fisheries. While studies have shown that reduced fishing pressure can lead to increases in biodiversity (Worm et al, 2006), carbon storage (Pershing et al, 2010), and the quality of recreational fishing (Hughes et al, 2005), these changes and their associated monetary values would require further study for the ETP prior to implementation of any policy based on this idea. Additionally, viewing the trade-off in this way does not consider societyspecific impacts of scaling back (e.g., economic impacts to Latin American fishers), which is a topic worth investigation.…”
Section: Trade-offs Among Ecosystem Servicesmentioning
confidence: 99%
“…The biological pump moves POC from the surface to deep ocean sediments through passive (e.g., sinking fecal pellets and ballasts) and active (e.g., vertical migrations by fish and zooplankton) transport (Eppley and Peterson, 1979;Ducklow et al, 2001;Henson et al, 2012;Davison et al, 2013). Additionally, carbon is stored in populations of large, long-lived vertebrates (e.g., apex predators), such as cetaceans and large fish; this is comparable to carbon being stored in large trees (Pershing et al, 2010). These important regulating services can be impacted by the use of provisioning services, particularly fisheries, which have the capacity to reduce populations of large consumer species and alter food web structure (Dayton et al, 1995;Jackson et al, 2001;Pauly et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation